Sphere‐Induced Rejuvenation of Swine and Human Müller Glia Is Primarily Caused by Telomere Elongation. (5th March 2017) - Xu, Ni; Chen, Yao; Dean, Kevin C.; Lu, Xiaoqin; Liu, Xiao; Wang, Wei; Dean, Douglas C.; Kaplan, Henry J.; Gao, Ling; Dong, Fangtian; Liu, Yongqing
Abstract: Müller cells are the major supportive and protective glial cells in the retina with important functions in histogenesis and synaptogenesis during development, and in maintenance of mature neurons as they show to secrete various cytokines and manifest potentials of self‐renewal and transdifferentiation into retinal neurons following injury in the vertebrate retinas. The swine retina has a visual streak structure similar to the human macular where cone photoreceptors are highly concentrated, thereby can serve as a better model for studying retinal diseases and for formulating cell‐based therapeutics than the rodent retinas. Like most differentiated somatic mammalian cells, the isolated swine and human Müller glia become senescent over passages in culture, which restricts their potential application in basic and clinic researches. Here, we demonstrate that the senescence of swine and human Müller cells is caused by telomere attrition upon multiplications in vitro; and the senescent cells can be rejuvenated by sphere suspension culture. We also provide evidence that sphere‐induced extension of telomeres in swine and human Müller glia is achieved by alternative lengthening of telomeres or/and by telomerase activation. Stem Cells 2017;35:1579–1591 Abstract : Primary swine and human Müller glial cells isolated from the adult retinal tissue and conditioned in vitro suffer a great deal of physical and physiological stresses causing telomere attrition and leading to either cell senescence or death. Sphere suspension culture activates telomere elongation and induces expression of stemness factors not only for rejuvenation of both swine and human Müller cells, but probably also for immortalization of swine Müller cells. At the end, the rejuvenated cells would die of cellular senescence when the entire survival population is distinct from their parental population—the swine Müller glia now have become swine sphere‐induced Müller glial stem‐like cells (siMGSC) that manifest higher potential to transdifferentiate and for self‐renewal.